Síntese, análise estrutural e aplicação de novos complexos de Manganês como miméticos da SOD - Kopp, Cristiéli Rossini (2012)
This work presents an study related to the synthesis and structural analysis of manganese complex with ligands of bases Schiff type, derivate from pyridoxine. Was used like starting material for the synthesis of ligands pyridoxine chlorhydrate and primary amines, with aromatic chain, in addiction the chloride, perchlorate and manganese acetate, for these complex synthesis. The synthesized compounds was: [Mn(pyr2etileno).2H2O]Cl (1), [Mn (pyr2etileno).H2O.MeOH]Cl (2), [Mn (pyr2pen).2H2O]ClO4 (3), [Mn2(pyr6but3)] (4), [Mn(pyr2aminoprop).H2O]ClO4 (5), [Mn(pyr2amimopropet)]ClO4 (6) and [Mn(pyr2piper)]ClO4 (7). Was made na strucural study of these compounds in solid state, was use X-ray diffraction in monocristal. For the superoxide dismutase (SOD) activity test of this complex was used these methods: ultraviolet and cyclic voltammetry. In addiction of, all the compounds was characterized through elemental analyses and infrared spectroscopy.